A Systematic Review of Neurofeedback’s Role in Alleviating Anxiety - Adineh, Hassan; Mazandarani, Omid; Seyyedrezaei, Seyyed Hasan; Barani, Ghasem (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to systematically evaluate the effectiveness, mechanisms, and clinical outcomes of neurofeedback interventions in reducing anxiety symptoms across clinical and subclinical populations.Methods and Materials: This systematic review was conducted following PRISMA 2020 guidelines and synthesized empirical evidence published between January 2018 and March 2025. Comprehensive searches were performed in PubMed, Scopus, Web of Science, PsycINFO, and the Cochrane Library using keywords related to neurofeedback, anxiety disorders, EEG, and real-time fMRI neurofeedback. After duplicate removal and multi-stage screening, 25 studies met inclusion criteria, comprising randomized controlled trials, controlled clinical studies, systematic reviews, and meta-analyses. Eligible studies included participants experiencing generalized anxiety disorder, social anxiety disorder, PTSD-related anxiety, test anxiety, chronic stress, or mixed anxiety presentations. Interventions involved EEG-based neurofeedback protocols (alpha–theta, SMR, beta training, frontal alpha asymmetry, individualized qEEG-guided training) and real-time fMRI neurofeedback targeting emotion-regulation networks. Data extraction captured study design, sample characteristics, neurofeedback modality, protocol parameters, outcome measures, and reported effect sizes. Methodological quality was evaluated using the Mixed-Methods Appraisal Tool and AMSTAR-2–aligned criteria, and findings were synthesized narratively due to heterogeneity across interventions.Findings: Across included studies, neurofeedback interventions produced statistically significant reductions in anxiety symptoms compared with baseline or control conditions, with moderate to large effect sizes reported in randomized trials and meta-analyses. EEG-based protocols demonstrated significant improvements in anxiety severity, attentional regulation, and emotional stability, while real-time fMRI neurofeedback yielded particularly large effects through modulation of amygdala and prefrontal–limbic connectivity. Multimodal approaches combining neurofeedback with mindfulness, CBT components, or HRV biofeedback showed enhanced treatment effects.Conclusion: Neurofeedback appears to be an effective non-pharmacological intervention for anxiety reduction, demonstrating reliable clinical benefits across diverse protocols and populations; however, greater protocol standardization.